2019
DOI: 10.1002/jctb.5953
|View full text |Cite
|
Sign up to set email alerts
|

Thiamethoxam removal by Fenton and biological oxidation

Abstract: BACKGROUND Thiamethoxam (TMX) is a potential insecticide pollutant of hydric resources that must be removed. Advanced oxidation processes (AOPs) are usually effective, but expensive to implement. Combining Fenton's reagent with biological oxidation circumvents the shortcomings of Fenton technology, facilitating the biodegradation of the resulting effluents in a sequencing batch reactor (SBR). RESULTS Fenton‐like oxidation of TMX with variable hydrogen peroxide (H2O2) doses afforded total organic carbon (TOC) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Also, an uncontrolled increase in peroxide doses can inhibit the generation of OH radicals (Chen et al 2007) as also reported in (Gomez-Herrero et al 2020). One aspect to highlight that has not been discussed in previous research is that the Fe2þ dose influences the reaction rate of the Fenton process, as reported by (Chen et al 2007), however, a concentration that does not affect bacterial growth must be guaranteed (Ballesteros Martín et al 2008a, 2008b, so optimizing this parameter in the experimental design contributes to significant improvements in the advanced oxidation process.…”
Section: Fenton/photo-fenton Coupling and Biological Processesmentioning
confidence: 82%
“…Also, an uncontrolled increase in peroxide doses can inhibit the generation of OH radicals (Chen et al 2007) as also reported in (Gomez-Herrero et al 2020). One aspect to highlight that has not been discussed in previous research is that the Fe2þ dose influences the reaction rate of the Fenton process, as reported by (Chen et al 2007), however, a concentration that does not affect bacterial growth must be guaranteed (Ballesteros Martín et al 2008a, 2008b, so optimizing this parameter in the experimental design contributes to significant improvements in the advanced oxidation process.…”
Section: Fenton/photo-fenton Coupling and Biological Processesmentioning
confidence: 82%
“…In a study performed by Gomez‐Herrero et al. (2020), the removal of the pure and commercial insecticide thiamethoxam (TMX) by Fenton‐like and Fenton‐biological oxidation was explored. For pure TMX, the Fenton process decreased the chemical oxygen demand (COD) by 80% and the total organic carbon (TOC) by 40%, while for commercial TMX, the COD and TOC reduction were 60% and 40%, respectively.…”
Section: Treatment Technologiesmentioning
confidence: 99%
“…In a study performed by Gomez-Herrero et al (2020), the removal of the pure and commercial insecticide thiamethoxam (TMX) by Fentonlike and Fenton-biological oxidation was explored. For pure TMX, the Fenton process decreased the chemical oxygen demand (COD) by 80%…”
Section: Ibumentioning
confidence: 99%
“…The latter seems to be more effective and has the potential for scale‐up applications. Another approach regarding the biodegradation of emerging pollutants was demonstrated by Gomez‐Herrero et al ., who worked with thiamethoxam (TMX), which is the first pesticide of the second generation of neonicotinoids . This group tested the performance of a combined Fenton–biological treatment for the removal of this pesticide from aqueous solutions.…”
mentioning
confidence: 99%
“…Another approach regarding the biodegradation of emerging pollutants was demonstrated by Gomez-Herrero et al, who worked with thiamethoxam (TMX), which is the first pesticide of the second generation of neonicotinoids. 3 This group tested the performance of a combined Fenton-biological treatment for the removal of this pesticide from aqueous solutions. Coupling those methods improved substantially the removal rates, while also limited down ecotoxic effects.…”
mentioning
confidence: 99%